Hiring migrant workers : restriction with reference to employment (Restriction) Act 1968 - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
The Employment (Restriction) Act 1968 regulates the employment of a non-citizen in any business, industry or undertaking whatsoever. The Act requires, inter alia, that the employment of a non-citizen in any business in the Federation must be upon the issuance of a valid employment permit. The employment permit so issued is only valid in respect of the particular employment and further, the employer specified therein. The employment permit, unless sooner cancelled or suspended, is valid for a period of not exceeding two years. The permit is non-transferable and thus, needs to be kept by the person upon whom the permit is issued. Employing or engaging a non-citizen without first obtaining a valid employment permit is an offence under the Immigration Act, 1959/63. Further, a person who knowingly harbours any other person whom he knows or has reasonable grounds for believing to have acted in contravention of the above 1959/63 Act, shall be guilty of an offence pursuant to s. 56(1)(d) of the 1959/1963 Act.